Electrophysiological and behavioral responses of Spodoptera littoralis caterpillars to attractive and repellent plant volatiles - Rharrabe, Kacem; Jacquin-Joly, Emmanuelle; Marion-Poll, Frédéric (Frontiers in Ecology and Evolution, 2014)
In Lepidoptera, the behavior of caterpillars to plant odors is poorly known. However, caterpillars are equipped with a reduced number of olfactory sensilla (3 on the antenna and 4-5 on the maxillary palps) which they can use to make fine discrimination between complex plant odors. In this work, we characterized behavioral responses of Spodoptera littoralis larvae to 11 odorants found in plants using binary choices in a Petri dish assay. In this assay, 1-hexanol, hexanal and cis-jasmone elicited a dose-dependent attraction, camphene and eugenol were repellent, while the response to other odorants were less marked. We recorded the electrophysiological responses to 5 of these odors from olfactory neurons of sensillum B2 of the antenna. Several neurons from this sensillum responded to each of the chemicals tested by an increase of their firing activity on top of a high background activity, suggesting that olfactory neurons of caterpillars is broadly tuned to a range of odorants rather than being specialized to a few molecules.